Performance of Pediatric Index of Mortality PIM-3 in a Tertiary Care PICU in India - Toteja, Nisha; Choudhary, Bharat; Khera, Daisy; Sasidharan, Rohit; Sharma, Prem Prakash; Singh, Kuldeep (Journal of Pediatric Intensive Care, 2021)
Pediatric index of mortality-3 (PIM-3) is the latest update of one of the commonly used scoring systems in pediatric intensive care. It has free accessibility and is easy to use. However, there are some skepticisms regarding its practical usefulness in resource-limited settings. Hence, there is a need to generate region-specific data to evaluate its performance in different case mixes and resource constraints. The aim of the study is to evaluate the performance of the PIM-3 score in predicting mortality in a tertiary care PICU of a developing country. This is a retrospective cohort study. All children aged 1 month to 18 years admitted to the PICU during the study period from July 2016 to December 2018 were included. We reviewed the patient admission details and the case records of the enrolled. patients. Patient demographics, disease profile, co-morbidities, and PIM-3 scores were recorded along with the outcome. Area under receiver operating characteristics (AUROC) curves was used to determine discrimination. Standardized mortality ratio (SMR) and Hosmer Lemeshow goodness of fit were used to assess the calibration. Out of 282 children enrolled, 62 (21.9%) died. 58.5% of the patients were males, and 60% were less than 5 years of age. The principal diagnoses included respiratory and neurological conditions. The AUROC for PIM-3 was 0.961 (95% CI [0.93, 0.98]) and overall SMR was 1.28 (95% CI [0.96, 1.59]). Hosmer-Lemeshow goodness-of-fit was suggestive of poor calibration (χ2 = 11.7, p < 0.05). We concluded that PIM-3 had good discrimination but poor calibration in our PICU setting.
Keywords: illness; outcomes; prognosis; scoring system; PIM-3; mortality; PICU